Hypromellose acetate succinate based amorphous solid dispersions via hot melt extrusion: Effect of drug physicochemical properties. (1st April 2020) - Sarabu, Sandeep; Kallakunta, Venkata Raman; Bandari, Suresh; Batra, Amol; Bi, Vivian; Durig, Thomas; Zhang, Feng; Repka, Michael A.
Highlights: Amorphous solid dispersions were prepared using HPMCAS via hot melt extrusion. NFD was solubilized better by HPMCAS grades compared to EFZ. Drug physicochemical properties affected the dissolution efficiency of polymer. Substitutions on polymer grade has significant effect on supersaturation maintenance. HPMCAS MG grade had greater supersaturation maintenance compared to LG and HG grade. Abstract: In this study, the impact of drug and hydroxypropyl methylcellulose acetate succinate (HPMCAS) grades physicochemical properties on extrusion process, dissolution and stability of the hot melt extruded amorphous solid dispersions (ASDs) of nifedipine and efavirenz was investigated. Incorporation of drugs affected the extrusion temperature required for solid dispersion preparation. Differential scanning calorimetry and powder X-ray diffraction studies confirmed the amorphous conversion of the drugs in the prepared formulations. The amorphous nature of ASDs was unchanged after 3 months of stability testing at 40 °C and 75% relative humidity. The dissolution efficiency of the ASDs was dependent on the log P of the drug. The inhibitory effect of HPMCAS on drug precipitation was dependent on the hydrophobic interactions between drug and polymer, polymer grade, and dose of the drug. The dissolution efficiency and dissolution rate of the ASDs were dependent on the log P of the drug and solubility and hydrophilicity of the polymer grade respectively. The inhibitory effect of HPMCAS on drug precipitation was dependent on the hydrophobic interactions between drug and polymer, polymer grade, and the dissolution dose of the drug.